AB0315 Racial Disparities in Patient Global Assessment May Lead to Misclassification of RA Disease Activity. (9th June 2015) - Jain, S.; Lundholm, A.; Bergman, M.
Abstract : Background: With current advancement in therapy of Rheumatoid Arthritis (RA), there is possibility of remission and low disease activity, leading to significant improvement in quality and quantity of life. Various studies in the past have shown that there is racial and ethnic disparity in reporting disease activity in RA. Our aim is to assess disparity in reporting "Patient Global" in White vs. Black patient population in a community based outpatient practice and also, its impact on disease activity measures, specifically CDAI. Methods: Data from random visits of 277 patients with confirmed RA was obtained from the practice database. Because of the small numbers of "other" groups, only data on Caucasian (n=191) and African-descent patients (n=36) was used. Regression analysis was used to determine impact of race on "patient global" after controlling for age, sex and disease duration. Using standard measures CDAI was calculated, which was then corrected for ethnicity. Results: After adjusting for age, sex, duration of disease, clinically meaningful and statistically significant results were seen for patient reporting "Patient Global". The mean Patient Global reported was 3.60 and 5.40 for White and Black population respectively. Patient Global was approximately 1.8 times higher in Black population compared to White population after controlling for age, sex and duration of disease. After using standard calculation for CDAI, 53% of white Population (101/190) were in remission or low disease activity vs. 37% of Black population (13/35) (p<0.05). However, after reducing the patient global by 1.80 in Black population, the corrected values for patient in remission or low disease activity as per CDAI was 53% Whites (101/190) vs. 49% Blacks (17/35) (p=0.33), which was no longer statistically significant. Conclusions: As per the data, 11% of Black population might have been miscalculated as not being in remission or low disease group, when they actually may have been. By using a "treat to target" strategy, we may be over treating >10% of Black population. Additional study and longitudinal research with larger numbers of patients and other localities will be required to improve the power of study. If substantiated, a method should be developed to correct these discrepancies to avoid over-treatment. References: EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying anti rheumatic drugs. Smolen JS, Landewe R, Breedveld FC, Dougados M, Emery P, Gaujoux-Viala C. Racial and ethnic disparities in disease activity and function among persons with rheumatoid arthritis from university-affiliated clinics. Barton JL1, Trupin L, Schillinger D, Gansky SA, Tonner C, Margaretten M, Chernitskiy V, Graf J, Imboden J, Yelin E. The Simplified Disease Activity Index (SDAI) and the Clinical Disease Activity Index (CDAI): a review of their usefulness and validity in rheumatoid arthritis. Aletaha D1, Smolen J Disclosure of Interest: None declared